Iowa RBA, August 25, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for August 25, 1998. Highlights include Eurasian Collared Dove, and Gray Partridge. Includes notes for update for August 26. Epson - sheet feed/flatbed